Alternate‐day dosing of caplacizumab for immune‐mediated thrombotic thrombocytopenic purpura. (23rd January 2022) - Kühne, Lucas; Kaufeld, Jessica; Völker, Linus A.; Wendt, Ralph; Schönermarck, Ulf; Hägele, Holger; Osterholt, Thomas; Eichenauer, Dennis A.; Bieringer, Markus; von Bergwelt‐Baildon, Anke; Fischereder, Michael; Buxhofer‐Ausch, Veronika; et al.
Abstract: Background: The anti‐von Willebrand factor (VWF) nanobody caplacizumab directly prevents the fatal microthrombi formation in immune‐mediated thrombotic thrombocytopenic purpura (iTTP), thereby adding a new therapeutic principle to the treatment of this disorder. However, real‐world treatment modalities beyond clinical trials remain heterogeneous. Methods: Here, we describe the risks and benefits of an alternate‐day dosing regimen for caplacizumab by thoroughly analyzing the timing and outcome of this approach in a retrospective cohort of 25 iTTP patients treated with caplacizumab at seven different medical centers in Austria and Germany between 2018 and 2021. Results: Alternate‐day dosing of caplacizumab appeared feasible and led to persisting normal platelet counts in most patients. Five patients experienced iTTP exacerbations or relapses that led to the resumption of daily caplacizumab application. VWF activity was repeatedly measured in 16 of 25 patients and documented sufficient suppression by caplacizumab after 24 and 48 h in line with published pharmacodynamics. Conclusion: Extension of caplacizumab application intervals from daily to alternate‐day dosing may be safely considered in selected patients after 3 to 4 weeks of daily treatment. Earlier modifications may be discussed in low‐risk patients but require close monitoring for clinical and laboratory features of thrombotic microangiopathy.